Reconstructing the feeding behavior of the dwarf Sicilian hippopotamus Hippopotamus pentlandi and the implications for Hippopotamidae paleodiets - Martino, Roberta; Rivals, Florent; Di Patti, Carolina; Pandolfi, Luca (Frontiers in Ecology and Evolution, 2026)
Hippopotamus pentlandi, the endemic dwarf hippopotamus of Sicily, represents one of the most iconic insular large mammals of the Mediterranean Basin. Despite the abundance of fossil remains, its feeding ecology and the environmental conditions of Sicily remain poorly understood. Here, we analyze dental microwear patterns of H. pentlandi teeth from three fossil-rich caves (Maccagnone, San Ciro, and Cannita) to reconstruct its diet and assess potential ecological adaptations. The results indicate a significantly higher number of pits compared to both extant H. amphibius and extinct continental taxa (H. antiquus, H. gorgops), suggesting greater ingestion of exogenous grit. The absence of puncture pits excludes a hard fruit feeding behavior, pointing instead toward a grazing diet influenced by increased dust intake. Differences in microwear among localities may reflect variable exposure to open, arid environments across Sicily during the Middle–Late Pleistocene. These findings suggest that H. pentlandi maintained a grazer-like feeding ecology similar to H. amphibius but adapted to drier and more terrestrial conditions, highlighting the role of insularity in shaping feeding behavior and habitat preference within Mediterranean hippopotamuses.